Integrated-electrochemical approaches powered by photovoltaic energy for detecting and treating paracetamol in water - Henrique, João M.M.; Monteiro, Mayra K.S.; Cardozo, Jussara C.; Martínez-Huitle, Carlos A. [UNESP]; da Silva, Djalma R.; dos Santos, Elisama V. [UNESP] (Elsevier, 2020)
Paracetamol is frequently used as an over-the-counter painkiller and is one of the most commonly consumed pharmaceuticals. Consequently, it is increasingly found in the natural environment, such as the water and soil. For this reason, the monitoring its concentration in water and the treatment of polluted effluents with paracetamol is a key issue to overcome urgently. Then, in this study, an electrochemical measuring device and electrochemical water treatment are integrated for their environmental application on paracetamol control. In the former, raw cork-graphite electrochemical sensor was prepared and a simple differential pulse voltammetric (DPV) method was developed for the quantitative determination of paracetamol. Meanwhile, the degradation of paracetamol was carried out with BDD anode by applying 15, 30, and 60 mA cm−2 and using different electrolyte concentrations of Na2SO4 (25, 50, 75, and 100 mM) over 240 min of treatment, in the latter. The decay and degradation of paracetamol were monitored by DPV, and HPLC measurements. Results indicated that, the electrochemical device exhibited a clear current response, allowing to quantify the analyte in the 2.5–1000 μM range, with limit of detection and quantification of 1.03 μM and 2.44 μM, respectively. Alternatively, BDD-electrolysis demonstrated to be an efficient process for removing organic matter from the pharmaceutical compound effluent via the production of strong oxidizing species. Lower paracetamol concentrations were detected, using the electrochemical sensor, when higher current densities and sulfate concentrations were used in BDD-electrolysis, demonstrating the applicability of integrated-technologies. The evolution of short-carboxylic acids (oxalic, formic, oxamic, maleic, acetic, and glycoxylic) was observed at 60 mA cm−2 and 100 mM of Na2SO4, but all of them were eliminated after 240 min. Inorganic ions (NH4+ and NO3−) were also detected under these experimental conditions, confirming that the pollutant was mineralized. Finally, lower energy requirements were estimated for all experimental conditions; however, solar photovoltaic (PV) renewable energy has been utilized to power these electrochemical technologies, decreasing the investment cost.
Keywords: Boron doped diamond; Cork; Electrochemical technologies; Paracetamol; Renewable energy; Sensor